Treatment of chronic inflammatory demyelinating polyneuropathy with high dose intravenous methylprednisolone monthly for five years: 10-Year follow up - (:unkn) unknown (ELSEVIER SCIENCE BV, 2014)
Objective: Although various modalities of treatment of chronic inflammatory demyelinating polyradiculopathy (CIDP) there are not any treatment protocol agreed. Materials and methods: We retrospectively evaluated the 20 CIDP patients (14 male, 6 female). Five patients were excluded from the study because they could not continue their treatments due to various problems during the treatment. The remaining 15 patients treated with monthly high dose intravenous methyl prednisolone for five years (IVMP) and followed up for 10 years. Results: The mean age of the patients was 48.1 +/- 14.6 years. The mean duration of disease was 6.8 +/- 3.1 years. We were found statistically significant difference between the pre-treatment and sixth month modified Rankin scores (p <0.001). Similarly, significant improvement was observed at the end of first, fourth and fifth years of treatment. Statistically significant difference was found between baseline and tenth year modified Rankin scores of 12 patients who were treated with only IVMP during 10 years follow-up. Conclusion: Long-term monthly IVMP pulse therapy seems to be very effective in the treatment of CIDP. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Chronic inflammatory demyelinating polyradiculopathy; Methylprednisolone; POLYRADICULONEUROPATHY; DEXAMETHASONE